Electrical restoration of the micturition reflex - Naumann, Stephen (Department of Electrical Engineering, 2016)
Numerous attempts at electrical stimulation of the detrusor muscle of the urinary bladder to evoke contraction and evacuation have been carried out over the past decade. A review of prostheses for the restoration of urinary continence and for effecting bladder evacuation, is given. Problems encountered during detrusor stimulation to effect voiding such as pain and increased urethral resistance are due to current spread to the surrounding pelvic structures. To restrict this current spread, sequentially activated multiple bipolar electrodes are employed. The development of a three-channel vesical stimulator to realize sequential pulsing is described. The inductively coupled device is externally controlled and totally implantable. The system used is believed by the author to be a unique method for transmitting three simultaneous and independent signals successfully to the simple type of receiver used. The good correlation between theoretical and practical results enables the theory developed to be used to predict the performance of coupled coils. The successful clinical trial of the stimulator in an animal and the good current restricting properties of the device indicate that the system used is a feasible method for the treatment of urinary retention following paraplegia.